(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The cervical spine’s anatomical structure is characterized by its close proximity to vital neural and vascular components. The vertebral arteries, spinal nerves, and spinal cord are directly adjacent to the intervertebral discs. Rapid changes in movement, such as sudden acceleration, deceleration, or sharp rotation, can cause these structures to impact the intervertebral discs. This can occur during activities like sports, passive neck movements or cervical spine injuries